2020
DOI: 10.1039/d0ra01465f
|View full text |Cite
|
Sign up to set email alerts
|

Double-edged effects and mechanisms of Zn2+ microenvironments on osteogenic activity of BMSCs: osteogenic differentiation or apoptosis

Abstract: Dual-directional regulation of diverse Zn2+ microenvironments on osteogenic activity of BMSCs plays important roles in the design of zinc-containing biomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 57 publications
(78 reference statements)
3
37
1
Order By: Relevance
“…However, moderate amounts of Zn ions can promote osteogenic differentiation of stem cells through upregulation of the ERK pathway, especially increasing the expression of RUNX2 [ 16 , 17 ]. In addition, similar to previous studies, Zn ions promoted osteogenic differentiation of stem cells when the concentration of Zn ions was less than 20 μg/mL [ 28 , 30 ]. Therefore, we have concluded that Zn ions delivered through the ZIOs promoted the early osteogenic gene expression and osteogenic differentiation capacity of hMSCs when treated with 5 μg/mL of ZIOs within 3 days.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…However, moderate amounts of Zn ions can promote osteogenic differentiation of stem cells through upregulation of the ERK pathway, especially increasing the expression of RUNX2 [ 16 , 17 ]. In addition, similar to previous studies, Zn ions promoted osteogenic differentiation of stem cells when the concentration of Zn ions was less than 20 μg/mL [ 28 , 30 ]. Therefore, we have concluded that Zn ions delivered through the ZIOs promoted the early osteogenic gene expression and osteogenic differentiation capacity of hMSCs when treated with 5 μg/mL of ZIOs within 3 days.…”
Section: Resultssupporting
confidence: 86%
“…Zinc ions also act as signaling molecules, affecting intracellular signaling pathways [ 27 ]. High concentrations of Zn ions not only decrease bone differentiation capacity, but also induce apoptosis [ 28 , 29 ]. However, moderate amounts of Zn ions can promote osteogenic differentiation of stem cells through upregulation of the ERK pathway, especially increasing the expression of RUNX2 [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The osteoconductive role of Zn 2+ on osteoblasts and mesenchymal stem/stromal cells is highly concentration-dependent [ 34 , 48 ]. The survival and proliferation of mesenchymal stem/stromal cells or MC3T3-E1 accrue in the range of 8 to 12 μM Zn 2+ [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, this pathway is known to stimulate the expression of genes such as BMP2, which is well-known to be involved in osteogenesis and bone formation (Kim et al, 2013 ). Low concentrations of zinc (2 and 5 μg/mL) have also been described to stimulate osteogenesis in rBMSCs through the activation of MAPK-ERK pathway (Yu et al, 2020 ). However, higher zinc concentrations (15 μg/mL) have been shown to induce cell apoptosis by ROS generation (Yu et al, 2020 ).…”
Section: Osteogenic Actionsmentioning
confidence: 99%
“…Low concentrations of zinc (2 and 5 μg/mL) have also been described to stimulate osteogenesis in rBMSCs through the activation of MAPK-ERK pathway (Yu et al, 2020 ). However, higher zinc concentrations (15 μg/mL) have been shown to induce cell apoptosis by ROS generation (Yu et al, 2020 ).…”
Section: Osteogenic Actionsmentioning
confidence: 99%